2018
DOI: 10.4172/jpb.1000484
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fat Storage-Inducing Transmembrane Proteins 1 and 2 as Putative Therapeutic Targets for Heart Failure by Integrated Analysis of Proteome and Transcriptome

Abstract: Cardiovascular disease constitutes a major health burden globally, for which novel cardiotonic agents are still required. Cardiac failure is thought to be caused by dysfunctions of the sarcoplasmic/endoplasmic reticulum (SR/ ER) in cardiomyocytes. Therefore, in this study, we searched for novel pharmaceutical targets in SR/ER. Tissue and organelle specific proteome profiling by liquid chromatography coupled with mass spectrometry after gel electrophoresis separation identified 3,638 proteins in heart and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It would be interesting to analyze the effects of their deletion in chronic heart failure induced by MI, and the mechanistic insights together with that in TAC model. Previously, we found that Fitm1 were identified by proteomic analysis of endoplasmic reticulum/sarcoplasmic rich fraction of mice heart, but there was no significant difference between TAC-operated and sham mice, probably because, the protein expression changed little as a result of TAC [9]. Therefore, it also would be important to analyze the detailed protein expression pattern in both heart failure model.
Fig.
…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It would be interesting to analyze the effects of their deletion in chronic heart failure induced by MI, and the mechanistic insights together with that in TAC model. Previously, we found that Fitm1 were identified by proteomic analysis of endoplasmic reticulum/sarcoplasmic rich fraction of mice heart, but there was no significant difference between TAC-operated and sham mice, probably because, the protein expression changed little as a result of TAC [9]. Therefore, it also would be important to analyze the detailed protein expression pattern in both heart failure model.
Fig.
…”
Section: Resultsmentioning
confidence: 94%
“…Recently, we found that these proteins were identified in mice and/or human heart samples by proteomic analysis, affected the cardiovascular system and body development in zebrafish, and that their modulated expression or function can change lipid droplet formation, ER function, and cellular metabolism in cells [9] . These data suggested their potential to modulate heart failure pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Compromised mitochondrial activity is a common feature in hearts under ischemic stresses, and an increase in mitochondrial biogenesis is considered a promising therapeutic strategy to treat ischemic heart disease 7 . FAM210A was previously reported to be reduced by 34% in murine hearts at the mRNA level under MI versus sham surgical conditions by a microarray-based transcriptome screening 32 . After examining the expression of FAM210A in human HF samples, we found that FAM210A protein expression was significantly decreased in the hearts of ischemic HF (IHF) patients compared to non-failing human hearts (Figure 7A).…”
Section: Fam210a Overexpression Alleviates Cardiac Pathological Remod...mentioning
confidence: 99%
“…The immunoprecipitated samples were separated by SDS-PAGE and gel portions corresponding to 150-200 kDa were excised. The in-gel digest was conducted as described [9]. For the multiple reaction monitoring (MRM) assay, the internal standard (IS) peptide mixture was spiked to the digested peptides.…”
Section: In-gel Digest Of Proteinsmentioning
confidence: 99%